Językowy obraz rzemiosła jako zawodu i źródła utrzymania (w świetle polskich przysłów i frazeologizmów) - Młynarczyk, Ewa (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The author of the article analyses set phrases that are motivated by the reality of the handicraft work. The analysis proves that Polish proverbs and set phrases depict work as an activity that is a sufficient and dependable source of income, evaluated on the basis of its effects. They also negatively depict people who perform their duties in a sloppy manner.